Quantitative comparison of Cone Penetration Testing (CPT) tip resistance data with Ground Penetrating Radar (GPR) amplitude data - McCallum, A B (Journal of Cold Regions Engineering, 2020)
Both cone penetration test (CPT) tip resistance data and ground-penetrating radar (GPR) amplitude data vary at the interface of snow layers of different density. Therefore, relationships between these data should be observable, enabling spatial extrapolation of CPT tip resistance values using GPR. Quantitative analysis of GPR amplitude data occurs in pavement analysis, but these techniques have not been applied to snow. GPR sounding using a commercially available ground-coupled 400 MHz antenna was conducted in the immediate vicinity of numerous CPT holes in Antarctic firn. Comparison between CPT tip resistance and GPR amplitude data reveals that extrapolation of point CPT resistance data is possible over large spatial areas by tracking GPR horizons that equate with CPT resistance value. In addition, GPR amplitude and polarity can reveal information about relative snowpack density. GPR can be used efficaciously with CPT snow resistance data, enabling efficient extrapolation of snow physical properties across large areas. Complementary use of GPR with CPT can enhance site investigation procedures for the development of polar infrastructure.